THE INTERDEPENDENCE OF MECHANICAL PROPERTIES AND PETROGRAPHIC CHARACTERISTICS OF ULTRAMAFIC ROCKS FROM GERANIA OPHIOLITIC COMPLEX - Giannakopoulou, P.P.; Tsikouras, B.; Hatzipanagiotou, K. (Bulletin of the Geological Society of Greece, 2016)
Ultramafic rocks from the Gerania Mountain ophiolite were tested as aggregates. Petrographic study through polarizing microscope enabled us to determine the presence of dunite, harzburgite and lherzolite. A series of mechanical tests were carried out in order to determine the suitability of these rocks in a wide range of applications. Dunite and harzburgite samples show higher values of uniaxial compression strength than the lherzolites, as the presence of joints and the higher degree of alteration significantly affects negatively this mechanical property in the last rock-type. The same factors influence the point load index, too. Serpentinization and the presence of soft and laminate minerals also exert a negative influence on the resistance on abrasion and attrition, as well as the grinding of the rocks. The same factors influence negatively the point load index, too.